Féminin-masculin - Guétat-Bernard, Hélène (éditions Quae, 2014)
Where are we today in the place of women in family agricultures compared with men, in both Northern and Southern countries. Based on very diverse field studies, this book exposes the need to analyse family agricultures from the perspective of masculine-feminine relations and social constructions that organise these power ratios. It addresses in succession the social management of male-female relationships in agriculture, gender inequalities in the definition and impact of agricultural and environmental policies and lastly the different approaches of gender in the food systems.